Answer:
15
Step-by-step explanation:
Answer:
B
Step-by-step explanation:
We can see in the expression that there are 2 x² blocks, 4 -x blocks, and 3 -1 blocks. Therefore, we can write this as
2 * x² + 4 * (-x) + 3 * (-1) = 2x²-4x-3
Comparing this with each answer, we have
A: x²-2x-4 + x² + 2x-1 = 2x²-5. This is not correct
B: 3x²-7x+1-(x²-3x+4) = 3x²-7x+1 -x²+3x-4 = 2x²-4x-3. This seems correct but we can check the other answers to be sure
C: (2x+1)(x-3) = 2x²-6x+x-3 = 2x²-5x-3. This is incorrect
D:
. This is incorrect
We can't answer the question, you haven't given us the information, we need to know what the x is here, or if they gave you a value.
If you are evaluating the answer is -41